1994
DOI: 10.1128/jvi.68.11.7221-7226.1994
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of HAM/TSP-like symptoms in WKA rats after administration of human T-cell leukemia virus type 1-producing cells

Abstract: Secreted polypeptides are a fundamental biochemical axis of intercellular and endocrine communication. However, a global understanding of composition and dynamics of cellular secretomes in intact mammalian organisms has been lacking. Here, we introduce a proximity biotinylation strategy that enables labeling, detection, and enrichment of secreted polypeptides in a cell type-selective manner in mice. We generate a proteomic atlas of hepatocyte, myocyte, pericyte, and myeloid cell secretomes by direct purificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
1

Year Published

1997
1997
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…A small animal model should be useful to study the pathogenesis of HTLV-1-associated diseases, which is not understood. Although rat models of HTLV-1 infection 9) and HAM/ TSP [10][11][12][13] have been reported, a mouse model would be desirable due to the accumulated information on the genetic background of mice and the advances in transgenic technology.…”
mentioning
confidence: 99%
“…A small animal model should be useful to study the pathogenesis of HTLV-1-associated diseases, which is not understood. Although rat models of HTLV-1 infection 9) and HAM/ TSP [10][11][12][13] have been reported, a mouse model would be desirable due to the accumulated information on the genetic background of mice and the advances in transgenic technology.…”
mentioning
confidence: 99%
“…In in vitro experiments, it was shown that HTLV-1 is able to infect a variety of cell lines, including B cells, endothelial cells, glial cells and fibroblasts. [5][6][7][8] Monkeys, rabbits and rats, besides humans, are susceptible to HTLV-1 infection, [9][10][11] but it was reported that the plating efficiency of vesicular stomatitis virus pseudotype bearing HTLV-1 envelope glycoprotein on mouse cells was approximately 1% of that on human cells. 12) There has been little work on experimental HTLV-1 infection in mouse.…”
mentioning
confidence: 99%
“…Using these susceptible animals, several animal models have been developed to study HTLV-1-associated diseases. The HAM/TSP-like disease model in rats of the WKA strain is well established and has been used to dissect the pathogenic mechanisms of the disease (14,23). On the other hand, a few ATL model systems have been established so far by using rabbits and rats, but their utility is limited.…”
mentioning
confidence: 99%